A simple tuning method for high temperature superconducting microstrip filters - Pal, S; Stevens, C; Edwards, D (2005)
In this paper we report a simple tuning methodology of high temperature superconducting (HTS) microstrip filters. In order to establish this new tuning approach a 5 pole lumped element HTS bandpass filter, centre frequency 800 MHz, narrowband (bandwidth, 7.6 MHz), is designed and fabricated on a 2 inch (diameter) Y Ba 2Cu 3O 6.94 thin film of thickness 700 nm and lanthanum aluminate (LaAlO 3) substrate of 0.5 mm thickness. The filter was etched using conventional photolithography and a wet chemical etching process. The 5 pole lumped element filter is tested in an integrated RF-cryocooler measurement system at 65 K and also in liquid nitrogen (77 K). We demonstrate a 19.3 MHz downward shift of the centre frequency of the 5 pole filter response. This is achieved by overlaying two layers of thin dielectric tape (PTFE) (50.0 νm thickness, permittivity 3.2) over the conducting patterned part of the filter surface. A full wave electromagnetic analysis of the dielectric environment of this tuning arrangement matches the measured response closely. To improve the passband response, the filter is tuned in liquid nitrogen, placing pieces of sapphire rods over the resonators of the filter layout. © 2005 IOP Publishing Ltd.